CSI Agent on a Mission Game App - CHING, Ju Mae Rosie (Institutional Knowledge at Singapore Management University, 2015)
CSI is a one-of-a-kind and first-ever iPad gaming app released early August, with the flash game at http://www.rosieching.com/csi. My primary objective was to realize my dreamed-up “MISSION STATISTICS” theme for students to apply their skills in hypothesis tests and linear regression. Another is the incorporation of their CSI results into an “enrichment 5%” of their grades. The harder an agent works, the higher his score, the sweeter the fruit of the labour which students always show massive enthusiasm for. It is also critical that students review their real-time progress, and I have ensured that in every step of each country’s mission. My other critical objectives are: Learn-as-you-play: the game empowers students to apply their knowledge acquired from class by immersing them in “Agent on a Mission” game setting, and hone their statistical skills through step-by-step, interactive game elements. Progressive Learning: I use a progression method through scores and star ratings. Students have to weave their way through with care in order to achieve higher scores and more stars. Self-Reflection & Competition: The feedback during and after the game allows each student agent to reflect on his own performance. The leaderboards also bring a competitive edge to the game.